Breast Milk and the Importance of Chrononutrition - Caba-Flores, Mario Daniel; Ramos-Ligonio, Angel; Camacho-Morales, Alberto; Martínez-Valenzuela, Carmen; Viveros-Contreras, Rubí; Caba, Mario (Frontiers in Nutrition, 2022)
During pregnancy the human fetus receives timed cues from the circadian rhythms of temperature, metabolites, and hormones from the mother. This influence is interrupted after parturition, the infant does not secrete melatonin and their circadian rhythms are still immature. However, evolution provided the solution to this problem. The newborn can continue receiving mother’s timed cues through breastmilk. Colostrum, transitional and mature human milk are extraordinary complex biofluids that besides nutrients, contains an array of other non-nutritive components. Upon birth the first milk, colostrum, is rich in bioactive, immunological factors and in complex oligosaccharides which help the proper establishment of the microbiome in the gut, which is crucial for the infants’ health. Hormones such as glucocorticoids and melatonin transfer from the mother’s plasma to milk and then the infant is exposed to circadian cues from their mother. Also, milk components of fat, proteins, amino acids and endogenous cannabinoids, among others, have markedly different concentration between day and night. In the present review we give an overview of nutritive and non-nutritive components and their daily rhythms in human milk and explore their physiological importance for the infant. Finally, we highlight some interventions with a circadian approach that emphasize the importance or circadian rhythms in the newborn for their survival, proper growth and development. It is estimated that approximately 600,000 deaths/year are due to suboptimal breastfeeding. It is advisable to increase the rate of exclusive breastfeeding, during the day and night, as was established by evolution of our species.